The Poynting Vector in the Ionosphere - Scott, J.C.W. (Proceedings of the IRE, 1950)
The equations of motion of ionospheric electrons in the field of plane electromagnetic waves subject to the frictional force of collision and to the force of the earth's magnetic field are developed in a form permitting graphical calculation of the wave polarization. The complex Poynting vector is then calculated in terms of the polarization, the complex refractive index, and a third function related to the forward tilt of the electric vector. Graphical integration is used to obtain curves representing the direction of energy flow for the ordinary and extraordinary modes, in a parabolic distribution of ionization for fixed values of geomagnetic latitude, collision frequency, and wave frequency for the case of vertical wave propagation. When collision is taken into account, the deflection has a small westward component for both ordinary and extraordinary modes. At zero collision frequency the deflections are in the vertical plane of the earth's field; the ordinary mode bending towards the poles and the extraordinary mode towards the equator. The normal ionization gradient with latitude, together with diurnal expansion and contraction of the ionized region, can explain the diurnal variation in the f z -f 0 critical frequency difference as due to the diurnal variation in the total path deflection.